Europe as a beacon of democracy? Citizenship policies relating to youth and migrants in Portugal - Ribeiro, N.; Malafaia, C.; Fernandes-Jesus, M.; Neves, T.; Menezes, I. (Journal of Civil Society, 2014)
This article aims to compare discourses about national and European policies on active citizenship and democratic participation, with a particular focus on youth and migrants. For this purpose we analysed official documents of public institutions and nongovernmental organizations (NGOs) in order to assess how the process of Europeanization has influenced national policies with regard to increasing political participation and citizens' civic awareness. Additionally, we conducted interviews with policy makers and NGO leaders in order to integrate and compare different levels of discourse and thus identify potential dissonances. Analysis of the documents shows that there is a strong concern to match national policy priorities with those established by international organizations. Notwithstanding positive perceptions, NGO leaders and policy makers criticize the ways policies have been implemented, stressing the need to adopt a strategy that bridges the gap between the prescribed and the real, as well as the importance of overcoming the hegemony of economic factors in policy decisions. In this regard, NGO leaders criticize the cynicism of political leaders and policies motivated by demographic and economic concerns. In relation to European identity and integration, NGO leaders argue that Europe must be collectively constructed; yet, policy makers stress that the failure of the Constitutional Treaty in 2005 resulted from a deficit in the negotiation process. In sum, this article suggests that it is necessary to promote greater involvement of civil society in the design and implementation of policies which, in turn, may contribute to the strengthening of shared democratic principles.